Horace: The Witness in Presence - Abderhalden, Rolf; Díaz, Bertha (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article focuses on the work developed by Mapa Teatro between 1993 and 1994 with eight inmates at La Picota Penitentiary Center, based on a text by Heiner Müller, Der Horatier , from 1976. During this time, an experimental community was constituted, moving between the prison and the theater. Mo- vement between real and imagined spaces led this group of inmates to become aware of their singularity and their relation to the anonymous potency of myth. It also led the directors of Mapa Teatro to ask about the function of witness in presence accomplished by the artist in the act of listening to life, and also to open up the question of whether the artist is or not “a worker of the social imagination” as the German director would have wanted.